1989
DOI: 10.1111/j.1751-1097.1989.tb02912.x
|View full text |Cite
|
Sign up to set email alerts
|

The Photophobic Response of Various Sulfur and Nonsulfur Purple Bacteria

Abstract: Abstract— The photophobic response of 34 strains of nonsulfur and sulfur purple bacteria was examined with respect to response‐eliciting light intensities. The bacteria were grown in defined synthetic media or in Winogradsky columns. Two population methods based on Engelmann's light trap were used to determine the discrimination thresholds of the bacteria. A single‐side irradiation method allowed the estimation of approximate values, while the double‐side irradiation method provided more exact values of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…response in this species, which was demonstrated by the accumulation of free-swimming bacteria in light spots projected into the suspension (this work) and by reversible migration into the light in a glass capillary partly covered with foil (17), correlates its wavelength dependence with the absorption spectrum of the photosynthetic pigments, as in Rhodospirillum rubrum (5). In addition, positive phototaxis in E. halophila was effective at a much lower light intensity than the negative phototactic response, which is in agreement with the observation that most purple sulfur bacteria, including members of the genus Ectothiorhodospira, show maximal positive phototactic sensitivity at 40 mW of white light m-2 (12). In order to determine the wavelength dependence of the negative phototactic response in E. halophila for comparison, light intensities between 14 and 23 W m-2 were used.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…response in this species, which was demonstrated by the accumulation of free-swimming bacteria in light spots projected into the suspension (this work) and by reversible migration into the light in a glass capillary partly covered with foil (17), correlates its wavelength dependence with the absorption spectrum of the photosynthetic pigments, as in Rhodospirillum rubrum (5). In addition, positive phototaxis in E. halophila was effective at a much lower light intensity than the negative phototactic response, which is in agreement with the observation that most purple sulfur bacteria, including members of the genus Ectothiorhodospira, show maximal positive phototactic sensitivity at 40 mW of white light m-2 (12). In order to determine the wavelength dependence of the negative phototactic response in E. halophila for comparison, light intensities between 14 and 23 W m-2 were used.…”
Section: Discussionsupporting
confidence: 73%
“…Subsequently, it was demonstrated that upon absorption of a photon, the protein enters a photocycle in which a long-lived photointermediate absorbing in the near UV decays thermally to the ground state on the seconds time scale (half-life = 0.7 s [22] halophila. It was known that E. halophila, like all motile purple phototrophic bacteria studied so far, shows a normal positive photophobic response to photosynthetically active light (2,12,17). In this report, we present evidence indicating that E. halophila, in addition, shows a repellent response at physiological light intensities.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…For this study, we focused our attention on photoactive yellow protein (PYP), a 14-kDa water-soluble blue-light receptor first discovered in Halorhodospira halophila (4), a purple sulfur bacterium that swims away from blue light and toward photosynthetically useful green light (5,6). Because its action spectrum for negative phototaxis matches the absorbance spectrum of PYP (6), this protein is presumed responsible for the signal that causes this extreme halophile to swim away from photons energetic enough to be genetically harmful.…”
mentioning
confidence: 99%
“…(termed by other authors "photophobotaxis"). If swimming cells experience diminishing light intensities, they stop and reverse their swimming direction, whereby Chromatium cells effectively accumulate at optimal irradiance (15,16,38). A combined effect of chemotaxis and photoresponses can be observed under the microscope.…”
mentioning
confidence: 99%